Thinking about the application of commercial cryptography in intelligent connected vehicles - Li, Yuning; Li, Kaitian; Shao, Xuebin (International Journal of Global Economics and Management, 2024)
As an important part of intelligent transportation, the information security of connected vehicles has become increasingly prominent. As a key technology to ensure the information security of networked vehicles, commercial cryptography plays an important role in vehicle identity authentication, data encryption and secure communication. In this paper, the status quo, challenges and future development trend of commercial cryptography application in connected vehicles are discussed, and some suggestions are put forward to strengthen technology research and development, standardization and industry cooperation. By continuously optimizing the application strategy of commercial cryptography, the information security level of connected vehicles can be effectively improved, providing strong support for the security development of the industry.